STRATEGI PENDIDIK DALAM MENGEMBANGKAN METODE PEMBELAJARAN PADA MATA PELAJARAN FIQIH DI MI AN-NIDZOM BABADAN TENGGER LOR KUNJANG KEDIRI - Muslih, Imam; Mustakim, Heri (Al Tadib : Jurnal Ilmu Pendidikan, 2014)
Teaching methods teachers use in every class meeting is not the origin of life, but after going through the selection corresponds to the formulation of a specially instructional purposes. Therefore, the teacher uses more than one method. The focus of this research is how the strategies used by teachers in teaching Fiqh and how teachers in developing learning methods Fiqh and anything what obstacles / barriers in the development of teaching methods in the Fiqh An MI An-Nidzom Babadan Tengger Kunjang Kediri and how the efforts of the teacher in the face. This type of qualitative field research (grounded) with descriptive phenomenological approach that produces descriptive data based on the phenomenon in the field. Data collection used by procedures, by interview, observation and documentation of the data sources that teacher and student of jurisprudence. The results of this study: 1) strategies of teachers in teaching jurisprudence, by designing a study that will be presented, giving stimulation and motivation so that students can focus and enthusiasm in learning, and to select and deterMIne the appropriate learning methods and in accordance with the teaching materials . 2) How teachers in developing learning methods Fiqh, namely: a) designing a learning device, identify learning goals, identify student activities, classroom management. b) observe the problems in the learning process to gain inspiration in the class method development. c) control of teaching and learning theory, master the subject matter and understand the learning styles of the learners. 3) Constraints/barriers in the development of teaching methods Fiqh, i.e. environmental factors and factors of infrastructure (facilities) are solved by providing motivation and self-protégé teachers to complete the required amenities.Keywords: strategy of learning, Development of method